2019
DOI: 10.3390/sports7030063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Caffeine Ingestion and Carbohydrate Mouth Rinse on High-Intensity Running Performance

Abstract: The aim of the current study was to investigate whether carbohydrate mouth rinsing works synergistically with caffeine to augment high-intensity running in a fed state. Eight participants completed a total of three trials; (1) placebo (PLA) trial (placebo capsule + placebo mouth rinse), (2) caffeine (CAF) trial (400 mg caffeine + placebo mouth rinse) and (3) carbohydrate mouth rinse + caffeine (CMR + CAF) trial (400 mg caffeine + 6% carbohydrate mouth rinse). Each trial consisted of a 45 min steady-state run a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Second, we did not ask the participants to keep a food diary, and did not place any restriction on the diet, including caffeine consumption. We do not know whether the participants had a high-carbohydrate diet or habitual caffeine consumption [39], and thus the results of our study may have been affected. It is possible that standardizing the diets of the participants may have enhanced our ability to detect more effects of the TRE intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not ask the participants to keep a food diary, and did not place any restriction on the diet, including caffeine consumption. We do not know whether the participants had a high-carbohydrate diet or habitual caffeine consumption [39], and thus the results of our study may have been affected. It is possible that standardizing the diets of the participants may have enhanced our ability to detect more effects of the TRE intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Fares and Kayser (2011) demonstrated significant performance benefits for fasted and fed states; however, MR in the fasted state resulted in an 11.6% increase in endurance capacity in a nonathletic population compared with 3.5% measured in the fed condition, with respect to PLA. Thus, the benefits of CHO‐MR may be more pronounced in a fasted state (Germaine, Collins, & Shortall, 2019); this situation is less practical, with lower ecological validity, than in a fed or postprandial state (Beelen et al, 2009). This tendency occurring in aerobic studies does not seem to be true for anaerobic performances.…”
Section: Discussionmentioning
confidence: 99%
“…An electroencephalography recording which has shown that while a CAF MR increases activity among the orbitofrontal and dorsolateral prefrontal cortex, a CHO MR only increases activity in the orbitofrontal cortex ( 47 ) suggests that there may be a summation effect of CAF and CHO. This postulation was debunked in a high-intensity running study whereby the summation effect of CHO + CAF MR did not significantly improve performance compared to CAF alone ( 52 ).…”
Section: Mouth Rinse Use In Sportmentioning
confidence: 99%